Pengaruh Stemming Nazief & Adriani terhadap Performa Algoritma Rabin-Karp dalam Mendeteksi Kemiripan Teks - Yulianto, Muhamad Arief; Nurhasanah, Nurhasanah (Jurnal Informatika Universitas Pamulang, 2021)
One of the information retrieval methods which be able to search root word of each word in document is stemming. Stemming process is done by eliminate prefixes, infixes, suffixes or confixes. Vega, Tala, Arifin and Setiono, Nazief and Adriani and Tala stemming are kind of Indonesian Language stemming. The method that is able to trace each character in sequence character is fingerprinting. Rabin-Karp algorithm is one of the fingerprinting method algorithms. This algorithm implement has function to process matching text/string, so it is really suitable to implement of text/string similarity detection. Researcher will analyze the effect of Nazief and Adriani stemming method to algorithm of Rabin-Karp performance to identify similarity of text/string. The researcher implemented datasets such as titles, keywords, introductions or abstracts from The Pamulang Informatics Engineering Journal which we had changed the wording. The result of the experiment data which has changed word order randomly that used stemming method has decreased 0.76% than without implemented stemming method. Furthermore, the experiment data which has been changed sentence order randomly has decreased 0.04% too.